Taxonomic review of the genus Hishimonus Ishihara (Hemiptera: Auchenorrhyncha: Cicadellidae: Deltocephalinae) from Korea - Kim, Eunji; Kim, Il-Kwon; Oh, Sumin; Jung, Sunghoon (Journal of Asia-Pacific biodiversity, 2024)
The species of genus Hishimonus Ishihara were reviewed including two new records from Korea: H. bucephalus and H. expansivus. Morphological descriptions, photographs of habitus and genitalia for each species are given. A key to males of Korean Hishimonus is provided.